Claret and present danger - Fox, Sarah (Mystery writer) (Fox, Sarah (Mystery writer). Literary pub mystery series., 2021)
Sadie Coleman, owner of a literary-themed pub in Shady Creek, Vermont, investigates after a Renaissance Faire "wizard" dies in the middle of his magic act